Analisis Sentimen terhadap Perpanjangan Masa Jabatan Presiden Indonesia Menggunakan Naïve Bayes - Zuhdi Hanif; Untung Surapati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Twitter social media is often used as a medium to express opinions on the government in Indonesia. There are also many controversial things on Twitter social media against the government, as is the case today there is a controversy wherethere is a proposal to make the term of office of the President in Indonesia three periods, which previously could only serve up to two terms or ten years. for one President. Public opinion or sentiment which in Twitter's terms is commonly referred to as